Strategi Pembelajaran Akidah Akhlak dalam Menanamkan Sikap Tanggung Jawab Santri Kelas VII MTs Nurul Ikhlas Sidoarjo - Abdillah, Chanif; Yusron, Muhammad; El-Yunusi, Maulana (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Instilling a sense of responsibility is the process of educating students to understand and carry out their obligations to themselves, others, and the environment. Teacher role models are very important, because students tend to imitate positive behaviors that they observe. Students can internalize a sense of responsibility as a habit. The purpose of this study was to analyze the learning strategy of aqidah akhlak in instilling a sense of responsibility in class VII students at MTs Nurul Ikhlas Sidoarjo. The research method used was qualitative with data collection techniques through observation, interviews, and literature studies. The data analysis techniques used were data reduction, data presentation, and drawing concslusions. The informants in this study were the Principal of MTs Nurul Ikhlas Sidoarjo on behalf of Nurul Rochmawati, S.Pd, the teacher of aqidah akhlak for class VII, namely Solikin, S.Pd, class VII students on behalf of Muhammad Mukhlash Miqdaad. The results of the study showed that teachers play a central role in guiding students by implementing four main strategies: role models, habits, motivation, and punishment. The instillation of a sense of responsibility is seen from the behavior of students in completing assignments, maintaining environmental cleanliness, and obeying school regulations. Through the implementation of this strategy, it is hoped that students can internalize good moral values ​​and apply them in everyday life, thus forming a responsible character.